2020
DOI: 10.1088/1742-6596/1567/4/042051
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of multicultural education through traditional games-based inquiry toward improving student scientific attitude

Abstract: Curriculum 2013 provides the opportunity for students to promote learning invites students to actively participate in learning activities, and fun for the learning activity. Lessons are taught by teachers also need to instill the character of the nation based on the principles of Pancasila. This is very important considering the development of information in the era of globalization led to the decline of morality in students, degradation students’ behaviour and identity of Indonesia. This study aimed to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
0
8
0
3
Order By: Relevance
“…Damayani et al, (2019) concluded that students playing traditional games in Indonesia gain values such as honesty, leadership, cooperation, and awareness. Healthy character development is provided for students who gain basic moral values through traditional games (Dewi et al, 2020;Lestari & Prima, 2017). Different traditional games develop different value judgments of students.…”
Section: The Role Of Experimental Groups In the Formation Of Value Pe...mentioning
confidence: 99%
“…Damayani et al, (2019) concluded that students playing traditional games in Indonesia gain values such as honesty, leadership, cooperation, and awareness. Healthy character development is provided for students who gain basic moral values through traditional games (Dewi et al, 2020;Lestari & Prima, 2017). Different traditional games develop different value judgments of students.…”
Section: The Role Of Experimental Groups In the Formation Of Value Pe...mentioning
confidence: 99%
“…If the technique is correct, the player's self-confidence will rise. That is why it is classified as an independent value [24]. Subsequently, the Gasing should be designed as attractive as possible before playing.…”
Section: Socialmentioning
confidence: 99%
“…Motivasi dapat memengaruhi apa yang kita pelajari, bagaimana kita belajar, dan kapan kita memilih untuk belajar (Alhabeeb & Rowley, 2018). Hal ini juga ditunjukan dari penelitian yang menjelaskan bahwa peserta didik yang termotivasi lebih cenderung melakukan kegiatan yang menantang, terlibat aktif, menikmati proses kegiatan untuk belajar dan menunjukkan peningkatan hasil belajar, ketekunan dan kreativitas (Dewi et al, 2020), selain itu, merancang lingkungan belajar yang memotivasi siswa akan menarik perhatian peserta didik (Anastasiadis et al, 2018).…”
Section: Pendahuluanunclassified